Reaping the Benefits of Deeper Euro-Med Integration Through Trade Facilitation - Yves Bourdet; Maria Persson (Lund University, School of Economics and Management, Department of Economics, 2011)
The current political turmoil in the Arab world has contributed to renewed interest in the Barcelona Process and how it can be improved in order to promote inclusive growth in the non-EU Mediterranean countries. In this paper, we explore whether deeper integration in the form of trade facilitation – i.e. improved and simplified trade procedures – could be an important part of a reform agenda. Adopting a Southern perspective by focusing on exports from non-EU Mediterranean countries to the EU, we use data from the World Bank's Doing Business Database on the efficiency of trade procedures to formally test whether the efficiency of trade procedures affects (i) bilateral volumes of exports, and (ii) the number of products that are exported. We find that improving export and import procedures to the best practice levels (for each group of countries) is likely to increase the value of non-EU Mediterranean exports by 34% and to increase the number of products exported by non-EU Mediterranean countries by 21%. A main implication of the results is therefore that more efforts should to be devoted to trade facilitation in order to reap the benefits of deeper integration between the two groups of countries.
Keywords: C23; F15; O24; 330; Barcelona Process; Mediterranean Union; European Union; Deeper Integration; Trade Facilitation; Export volumes; Export Diversification